RESPONS PESERTA DIDIK TERHADAP MODUL KINGDOM MONERA SEBAGAI BAHAN AJAR BIOLOGI KELAS X SMA/MA - Meilisa Ella Putri; Laili Fitri Yeni; Reni Marlina (FKIP Universitas Tanjungpura, 2020)
This study aimed to determine the feasibility and response of students to the module of kingdom monera as teaching material for class X SMA/MA. The research take form as descriptive research using survey methods. The samples in this study were high school students in class XI consisting of 34 students from SMA 2 Pontianak, 21 students from SMA Muhammadiyah 2 Pontianak, and 25 students from SMA Koperasi Pontianak. The research instruments in this study were the kingdom monera module validation sheets and the student response questionnaire validated by 5 validators. The kingdom monera module validation sheet consists of 4 aspects namely content eligibility, language, content and graphics. Student responses questionnaire consisted of 3 aspects namely cognitive, affective and conative aspects consisting of 25 statement items and divided into 13 positive statements and 12 negative statements. Data analysis technique to determine the feasibility of the module using the CVI formula and student questionnaire responses using a Likert Scale. The kingdom monera module validation obtained a CVI value of 1,00 and was considered valid. The results of the analysis of the overall response questionnaire were 81.76% with a very strong category and consisted of cognitive responses at 80,93%, affective responses at 82,15%, and conative responses at 82,19%. Overall the kingdom monera module was appropriate to be used as teaching material in the kingdom monera material.